Perceived Value of Health Insurance and Enrollment Decision among Low-Income Population - Jayoung Han (University of Minnesota Libraries Publishing, 2018)
The individual mandate is one of the key features of the Affordable Care Act (ACA) and has contributed to a substantial decrease in the overall uninsured rate. We examined the relationship between the individual's insurance status and his/her attitude towards risk and uncertainty among the nonelderly adults, without employer-sponsored insurance (ESI) sources and who are most likely to benefit from the ACA. A descriptive, cross-sectional study was conducted using the 2014 full-year consolidated data file from the Household Component of the Medical Expenditure Panel Survey-Household Component (MEPS-HC). This study included 4,848 individuals, aged 18-64 years, with incomes between 138-400 % of the Federal Poverty Level (FPL), and without access to public coverage or ESI. We examined the factors associated with the likelihood of being uninsured using a logit model. We found that the proportion of the uninsured among the low-income nonelderly adults without ESI (31.1%) was much higher than the one among the nonelderly adults (14.3%). The uninsured adults were likely to have lower demand for insurance and perceived value of insurance and were less likely to visit a doctor or to fill prescription drugs. More rigorous outreach efforts focusing on increasing perceived value of health insurance could contribute to an increased insurance coverage among low-income populations.   Type: Original Research